Vertical transmission of scrub typhus: a case report of congenital infection - Yonghan Luo; Zhenghui Liao; Xianyao Yang; Hechun Li; Jinyu Chi; Zhifang Cha; Jun Liu; Chuangang Ding; Yue Feng (Emerging Microbes and Infections)
Scrub typhus (ST), caused by Orientia tsutsugamushi, is typically transmitted through mite bites, but vertical transmission from mother to infant remains poorly understood. This case presents a 13-day-old female neonate diagnosed with congenital ST. The infant developed severe systemic involvement, including fever, jaundice, respiratory distress, and signs of hemophagocytic lymphohistiocytosis (HLH). Despite broad-spectrum antibiotic therapy, her condition worsened. PCR and serological tests confirmed the diagnosis of ST in both the neonate and the mother, with IgM positivity indicating congenital infection. Following treatment with doxycycline, the patient's condition improved. This case adds to the growing body of evidence supporting the vertical transmission of ST and highlights the need for increased awareness of congenital ST.